Advancing Surgical and Medical Education: Insights and Lessons from Neurosurgery in Pakistan - Irshad, Hammad Atif; Anwar, Eman; Shaikh, Taha; Ashfaq, Dahir; Shakir, Muhammad; Enam, Syed Ather (Asian Journal of Neurosurgery, 2025)
In this article, we have summarized the current landscape of neurosurgical education in Pakistan, highlighting key gaps in training, mentorship, and academic resources. In this narrative review, we explore original articles and reviews that discussed the factors affecting the surgical and medical education in Pakistan, published between January 2000 and July 2025. At the undergraduate level, exposure to surgical subspecialties like neurosurgery is often limited and inconsistent, which may affect students' interest in pursuing such fields. Postgraduate training programs also exhibit significant variation in the quality of mentorship, academic activities, and access to modern teaching resources like simulation-based learning.Based on the latest assessment of medical education pertaining to neurosurgery in Pakistan, recommendations for the way forward are provided in this article.
Keywords: clinical curriculum; developing country; medical education; Pakistan; surgical education